2020
DOI: 10.1002/er.6208
|View full text |Cite
|
Sign up to set email alerts
|

Techno‐economic planning of local energy systems through optimization models: a survey of current methods

Abstract: Summary Energy system planning is a difficult task, since it involves long‐term decision‐makings with multiple dimensions: technical, economic, social, ecological, and political. The rise of distributed and multi‐energy systems including new technologies has further increased this complexity. Techno‐economic studies based on optimization models have recently received much attention in the literature. They are essential to grasp energy systems complexity and provide decision support. This work targets methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 133 publications
0
12
0
Order By: Relevance
“…4.2.2 Single large linear optimization problem. When the anticipative strategy is embedded in the design procedure, a single large linear optimization (LP) problem is formulated and solved by calling an external solver (for instance, see Cuisinier et al, 2021, for more details). The solver not only computes the optimal sizes but also the optimal power flow decisions at each time step and for each scenario.…”
Section: Resolution Methodsmentioning
confidence: 99%
“…4.2.2 Single large linear optimization problem. When the anticipative strategy is embedded in the design procedure, a single large linear optimization (LP) problem is formulated and solved by calling an external solver (for instance, see Cuisinier et al, 2021, for more details). The solver not only computes the optimal sizes but also the optimal power flow decisions at each time step and for each scenario.…”
Section: Resolution Methodsmentioning
confidence: 99%
“…After reviewing the literature of energy system and storage expansion planning (Haas et al, [3], Koltsaklis et al, [4]), interacting with the open energy modeling community (OpenMod, [5]), examining the different methodologies developed (Cuisinier et al, [6]), we observed that most research efforts are focused on optimizing the sizing, investment and operation of a given energy system at different horizons. These approaches enable to assess the evolution of a system, to find the best decision-making in an uncertain environment [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the electrical power supply service has become a concern not only for the companies providing this service, but also for consumers connected to the energy grid. 1,2 This concern is mainly due to the consequent increase in the use of computerized systems, which demand greater stability and continuity in the supply of energy, guaranteeing the proper functioning and useful life of the exploited equipment. In order to increase customer satisfaction, energy companies have invested in their network infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main investments is the implementation of smart automation systems aiming at the improvement, reliability and operational efficiency of the energy distribution systems. 1,3 Focusing on energy distribution quality, the challenge arises of implementing an economically viable technology that provides the management and control of the energy distribution network. For this purpose, the concept of smart electrical networks, commonly known as smart grids, is idealized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation